Factors associated with the interruption of contraceptive use during the COVID-19 pandemic in Peruvians, 2020 - Valverde-Espinoza, Natalia Marisol (2021)
Introduction: The COVID-19 pandemic has impacted on women's sexual and reproductive health, since it affected the provision of family planning services; and, therefore, the continuity of the use of contraceptive methods, being important to know what factors were related to this fact. Objective: To determine the factors associated with the interruption of contraceptive use during the COVID-19 pandemic in Peruvians, 2020. Materials and Methods: Type of quantitative study with observational, analytical and cross-sectional design, the sample included 342 women, Women residing in Peru, between 18 and 45 years old, who were using a contraceptive method before quarantine for COVID-19, participants with incomplete and inconsistent data and adolescents were excluded. A questionnaire by social networks validated by experts was applied, the variable factors included: personal, reproductive and informative, as well as the interruption of contraceptive use, the association was determined through Pearson's chi square, with a confidence level of 95 %. In addition, it had ethical approval. Results: 45% of users interrupted the use of contraceptives during the quarantine due to COVID-19. The personal factors associated with the interruption of contraceptives were: age (p = 0.044), place of residence (p = 0.026), marital status (p <0.001); the reproductive ones: parity (p <0.001), having sexual relations (p <0.001) and information: searching for information through digital means (p = 0.044). The main reason for discontinuing use was fear of contagion by COVID-19 (42.8%). Conclusions: Almost half of the contraceptive users interrupted their use during quarantine due to COVID-19, and the factors associated with said interruption were personal, reproductive and informative in nature. Therefore, it is necessary for health personnel to provide comprehensive care for women, especially in health emergencies.